LEGAL RELATIONSHIP BETWEEN DOCTORS AND PATIENTS IN MEDICAL SERVICE EFFORTS - Endang Kusuma Astuti (Diponegoro Law Review, 2017)
The relationship between doctor and patient is not equal. The relationship between doctor and patient gave birth to the legal aspects of which object of inspanningsverbintenis is maximum efforts for the recovery / maintaining the health of patients which performed with caution based on the knowledge and experience of the doctor to seek recovery of the patient. Legal relationship between doctor and patient in medical care effort began when the patient filed a complaint which responded to by a doctor. Doctor’s responsibility in medical services efforts include ethical, professional, and legal responsibility, which covers doctor’s responsibility related to criminal law, civil law and administrative law